Health promotion of inclusive WASH Facilities on outpatient satisfaction - Rolia, Eva; Karyus, Aila; Yudhinanto, Yudhinanto; Budiati, Endang; Fansuri, Muhaimin; Sky, Monica Werin; Irawan, Hengki (Community Research of Epidemiology (CORE), 2024)
Health facilities are places that are frequently visited by the public for treatment, maternal and child examinations, vaccinations and routine check-ups. However, people face an increased risk of infection if they receive treatment in health facilities that lack basic needs related to Water, Sanitation, Hygiene (WASH). Health facilities also still pay less attention to other inclusive indicators such as women, the elderly and children. Therefore, this study aims to analyze the influence of patient education, monitoring programs, and promotion of healthy lifestyles regarding inclusive WASH on the satisfaction of outpatients at RSUD Jend. Ahmad Yani, Metro City in 2024. This type of research uses a quantitative approach with data analysis using univariate, bivariate and multivariate tests. The results of the study explain the level of satisfaction of outpatients at RSUD Jend. A. Yani Metro City in 2024 is at a level of 36%, bivariate analysis shows that only promotion of a healthy lifestyle has a significant relationship with the level of patient satisfaction (P-Value = 0.000 < 0.05). Multivariate test results explain that only monitoring program variables and healthy lifestyle promotion variables regarding inclusive WASH facilities have an influence on patient satisfaction. The dominant variable that influences the level of patient satisfaction is the promotion of a healthy lifestyle. With a focus on promoting healthy lifestyles and optimizing WASH facility monitoring programs, RSUD Jend. A. Yani can increase patient satisfaction significantly. Implementing appropriate policies based on these findings will help hospitals provide better health services and meet patient expectations.